Tonga : 2008 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2008)
This 2008 Article IV Consultation highlights that Tonga's economy has shown resilience in the aftermath of the November 2006 riots and is now on a path to recovery. The key factor underpinning this resilience has been private investment. Donor-supported government reconstruction loans are expected to add further momentum to the recovery. However, the global upswing in fuel and food prices has intensified pressure on inflation and external reserves. Tonga's external position is expected to weaken, reflecting mainly the impact of rising food and fuel prices.